PREVALÊNCIA E PREDITORES DO USO INCORRETO DOS DISPOSITIVOS INALATÓRIOS EM PACIENTES PORTADORES DE DOENÇA PULMONAR OBSTRUTIVA CRÔNICA - Giovanna Agda Moraes Mesquita; Jéssica Souza Ferro; Roberta Martins Carlos Alves; José Laerte Rodrigues da Silva Júnior; Carolina Gomes Machado (UniEVANGÉLICA, 2015)
Objective: To determine the prevalence and predictors of incorrect use of inhalers in ambulatory patients with chronic obstructive pulmonary disease (COPD). Methods: We conducted a crosssectional study in COPD patients attending an out-patient primary health unit of in Anápolis- Goiás. Results: The average number of errors was statistically different in relation to the number of devices in use (p = 0.02). It was observed that the mean error between the group that used one inhaled device was significantly lower than the group that used three inhalers devices. A correlation analysis showed that there was a negative correlation between the number of errors and post BD FEV1 in liters (r = 0.55; p = 0.004), and a linear regression showed that the number of errors can be predicted using pos-BD FEV1 in liters (p = 0.004), being inversely related to number of errors when using the device. Conclusion: We conclude that the number of inhalers and severity of respiratory disease are predictors of incorrect use of inhalation devices in patients with COPD